Model eliciting activities in mathematics learning: Epistemological beliefs - Vera Dewi Susanti; Rochmad Rochmad; Isnarto Isnarto; Sebastian Fedi; Ririn Hutneriana (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to determine epistemological beliefs, beliefs in learning mathematics with eliciting activities model, and the relationship between the two on prospective mathematics teachers. Quantitative research method using a survey, which was conducted on 52 students of prospective mathematics teachers. Data collection is done by using a questionnaire. This study uses a questionnaire from TEDS-M which investigates the beliefs of prospective mathematics teachers about teaching mathematics. Data analysis will be carried out quantitatively, both descriptively and by correlation. The results showed that 1) mathematics teacher candidates had mixed beliefs, namely static and dynamic, but more static beliefs about the dominant mathematical epistemology: 2) The application of eliciting activities model learning, mathematics teacher candidates had mixed beliefs, namely conventional and constructive, but more on dominant constructivist beliefs and 3) practical implications for prospective mathematics teachers and the application of learning models must begin with testing or understanding the beliefs of prospective mathematics teachers regarding the epistemology of mathematics.